Penguatan Toleransi Beragama Melalui Program Harmoni Antar Agama di Tingkat Komunitas - Chandra, Erbin; Gultom, Syawal; Dharma, Edy; Sherly, Sherly (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The Building Harmony Among Religions: Strengthening Religious Tolerance at the Community Level program aims to enhance public understanding and awareness of the importance of religious tolerance through interfaith dialogue. This research is driven by the increasing need for social harmony amidst the religious diversity present in Indonesian society. The primary objective of this study is to explore how community service activities can strengthen the values of religious tolerance at the community level and create interfaith collaboration networks. The research employs a qualitative approach with data collection techniques such as questionnaires, in-depth interviews, and participatory observation during the program's implementation. The results show that the program successfully increased participants' understanding of the importance of tolerance, strengthened interfaith relationships, and encouraged collaborative actions in addressing social issues. However, challenges remain in overcoming the exclusive attitudes of some participants and the limited time frame, which restricted the program's reach. The conclusion of this study is that the religious tolerance strengthening program is highly effective in enhancing interfaith harmony at the community level, but to expand its impact, program sustainability and support from various parties are needed.ABSTRAKProgram Membangun Harmoni Antar Agama: Program Penguatan Toleransi Beragama di Tingkat Komunitas bertujuan untuk meningkatkan pemahaman dan kesadaran masyarakat tentang pentingnya toleransi beragama melalui dialog antaragama. Penelitian ini dilatarbelakangi oleh meningkatnya kebutuhan akan kerukunan sosial di tengah keberagaman agama yang ada di masyarakat Indonesia. Tujuan utama penelitian ini adalah untuk mengeksplorasi bagaimana kegiatan pengabdian masyarakat dapat memperkuat nilai toleransi beragama di tingkat komunitas dan menciptakan jejaring kolaborasi lintas agama. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan teknik pengumpulan data berupa kuesioner, wawancara mendalam, dan observasi partisipatif selama pelaksanaan program. Hasil penelitian menunjukkan bahwa program ini berhasil meningkatkan pemahaman peserta tentang pentingnya toleransi, mempererat hubungan antar umat beragama, dan mendorong aksi kolaboratif dalam menyelesaikan masalah sosial. Namun, masih terdapat tantangan dalam mengatasi sikap eksklusif dari sebagian peserta dan keterbatasan waktu yang membuat jangkauan program terbatas. Kesimpulan dari penelitian ini adalah bahwa program penguatan toleransi beragama sangat efektif dalam meningkatkan keharmonisan antaragama di tingkat komunitas, namun untuk memperluas dampaknya, dibutuhkan kesinambungan program dan dukungan dari berbagai pihak.